Impact of chronobiological variation in Takotsubo Syndrome: prognosis and outcome - El-Battrawy, Ibrahim; Aweimer, Assem; Lang, Siegfried; Ansari, Uzair; Gietzen, Thorsten; Ullrich, Niklas; Mügge, Andreas; Zhou, Xiao-Bo; Borggrefe, Martin; Akın, Ibrahim (Frontiers in Cardiovascular Medicine, 2021)
Background: A considerable amount of evidence has shown that acute cardiovascular diseases exhibit specific temporal patterns in their onset.Aim: This study was performed to determine if takotsubo syndrome (TTS) shows chronobiological variations with short and long-term impacts on adverse events.Design: Our institutional database constituted a collective of 114 consecutive TTS patients between 2003 and 2015.Methods: Patients were divided into groups defined by the onset of TTS as per time of the day, day of the week, month and quarter of year.Results: TTS events were most common afternoon and least common in the night, indicating a wave-like pattern (p = 0.001) of manifestation. The occurrence of TTS events was similar among days of the week and weeks of the month. TTS patients diagnosed in the month of November and subsequently in the fourth quarter showed a significantly longer QTc interval. These patients also revealed a significantly lower event-free-survival over a 1-year follow-up. In a multivariate Cox regression analysis, TTS events occurring in the fourth quarter of year (HR 6.8, 95%CI: 1.3-35.9; p = 0.02) proved to be an independent predictor of lower event-free-survival.Conclusions: TTS seems to exhibit temporal preference in its onset, but nevertheless this possibly coincidental result needs to be analyzed in a large multicenter registry.
Gesehen am 26.10.2021